The long-term impact of multisystemic therapy: an experiential study of the adolescent-young adult life transition - Conroy, Dom; Smith, Jonathan A.; Butler, Stephen; Byford, Sarah; Cottrell, David; Kraam, Abdullah; Fonagy, Peter; Ellison, Rachel; Simes, Elizabeth; Anokhina, Alisa (SAGE Publications, 2021)
This qualitative study examines the possible long-term impact of multisystemic therapy (MST) as young people experience the transition from adolescence to young adulthood. MST is an intensive intervention aimed at reducing antisocial behavior among young people. Interviews were conducted with 32 young people aged 16 to 22 years at their 48-month follow-up as part of the Systemic Therapy for At-Risk Teens (START) evaluation trial in the United Kingdom. Sixteen participants had received MST while 16 received management as usual (MAU). Interviews addressed participants’ current life experiences and were analyzed with interpretative phenomenological analysis (IPA). The inductive qualitative analysis data were transformed into numerical data. Interview extracts were coded as either forward-looking and hopeful (“mature”) or static and frustrated (“stuck”). Among males, significantly more mature outcomes were found among participants who had received MST compared with MAU. No differences were seen between the female groups. A detailed qualitative commentary shows how the constructs, mature and stuck, are manifest across the four domains. The findings suggest that working with an MST therapist during adolescence helped young men cultivate more mature, forward-looking viewpoints and life activities 4 years later when transitioning into adulthood. Findings are discussed in relation to relevant theory and practical applications.